Buckling and vibration analyses of composite laminates with weak interfaces by a coupled meshfree and finite element method - Chen Jie; Wang Hai; Wang Jie (Science and Engineering of Composite Materials, 2016)
Buckling and free vibration analyses for composite laminates with weak interfaces were performed based on a three-dimensional hybrid semianalytical model. The model was established by coupling the radial point interpolation method and finite element method (FEM) in a Hamilton system. A direct coupling approach was developed based on the FEM background cell algorithm, and a modified Hamiltonian function for buckling analysis of rectangular laminated plates was given. The governing equations were deduced with the transfer matrix technique and a general linear spring layer model based on the modified Hellinger-Reissner variational principle. Several numerical examples are also presented to validate the efficiency and accuracy of the present method.